2001
DOI: 10.1002/yd.23320019005
|View full text |Cite
|
Sign up to set email alerts
|

Persons with severe mental illness in jails and prisons: A review

Abstract: One of the greatest problems of deinstitutionalipation has been the very large number ofpersons with severe mental illness who have entered the criminal justice system instead of the mental health system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
219
2
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(229 citation statements)
references
References 69 publications
4
219
2
4
Order By: Relevance
“…This finding should be interpreted cautiously, however, given that mental illness could only be ascertained in the data available for this study if a study group member's prison stay was directly before or after their stay in a mental health facility. Only 1.1% of the study was identified as mentally ill by this measure, a proportion that, according to the research in forensic mental health, vastly under-represents the number of persons with severe mental illness among incarcerated populations (Lamb and Weinberger, 1998). The unavailability of clinical measures of mental illness (as well as for substance abuse) is one of the limitations of this study, and it stands counter to the large degree of attention these issues have received in research on both incarceration and homelessness.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 95%
See 1 more Smart Citation
“…This finding should be interpreted cautiously, however, given that mental illness could only be ascertained in the data available for this study if a study group member's prison stay was directly before or after their stay in a mental health facility. Only 1.1% of the study was identified as mentally ill by this measure, a proportion that, according to the research in forensic mental health, vastly under-represents the number of persons with severe mental illness among incarcerated populations (Lamb and Weinberger, 1998). The unavailability of clinical measures of mental illness (as well as for substance abuse) is one of the limitations of this study, and it stands counter to the large degree of attention these issues have received in research on both incarceration and homelessness.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 95%
“…Burt et al (2001) paints an even bleaker economic picture for the homeless, showing median household income to be less than 50% of the poverty income guidelines, with less than half of the households (i.e., families or individuals) having any income from employment and less than 20% with any type of job that could be considered permanent. High rates of mental illness and substance abuse have also been widely documented in research on both populations (Burt et al, 2001;Conklin et al, 2000;Freudenburg, 2001;Lamb 1998;Peters et al, 1998). Finally, this convergence of characteristics also manifests spatially, as both incarceration and homelessness disproportionately affects persons in low-income urban black neighborhoods (Correctional Association of New York, 1990;Culhane et al, 1996;Wacquant, 2000).…”
Section: Introductionmentioning
confidence: 96%
“…Also, police, who see troublesome situations through the lens of their role as "law enforcers" are motivated to maintain their authority in conflict situations, often invoking the power of arrest to do so. These processes have led some to argue that mental illness has been "criminalized," with mentally ill suspects more likely to be arrested than suspects who are not mentally ill (Lamb and Weinberger, 1998;Lamb et al, 2002;Steury, 1991;Teplin, 1990).…”
Section: The "Criminalization" Of Mental Illnessmentioning
confidence: 99%
“…Additionally, the mental health of incarcerated women is poorer compared with nonincarcerated women. Emotional and physical abuse, posttraumatic stress disorder, depression, anxiety and substance abuse are commonly reported (Fogel & Belyea, 2001;Lamb & Weinberger, 2001;Young & Reviere, 2005).…”
Section: Women and Incarcerationmentioning
confidence: 99%